Analisis Peran Pelayanan Pemerintahan Desa terhadap Perkembangan Desa Mekarwangi Kecamatan Cisauk - Erika Noviyanti; Rustam Nawawi; Khikmawanto Khikmawanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the role of village government services in the development of infrastructure in Mekarwangi Village, Cisauk District. This research uses a descriptive qualitative approach with data collection methods through interviews with ten local residents. The results of the study show that village government services have made a significant contribution to the village's physical development, particularly in improving the accessibility and quality of basic infrastructure. Before 2015, road access in the village still used simple asphalt and lacked adequate drainage systems. Since 2016, the village government has begun concrete paving of roads and construction of drainage channels. Then, in 2022, road development using paving blocks was carried out in small alleys to facilitate mobility for residents, especially those living near plantation areas. Eight out of ten respondents stated that the development was very helpful, as previously they faced difficulties due to slippery and unsafe dirt roads, especially during the rainy season. These findings indicate that appropriate and responsive village government services can drive development that directly impacts the improvement of rural community quality of life.